Patient Preference of Apalutamide Versus Enzalutamide for Recurrent or Metastatic Hormone-sensitive Prostate Cancer: An Open-label, Randomized, Crossover Trial - Ng, Chi-Fai; Yee, Chi-Hang; Chiu, Peter Ka-Fung; Wong, Kenneth; Lam, Daisy; Yuen, Violet Wai-Fan; Lai, Pui-Tak; Teoh, Jeremy Yuen-Chun (European urology oncology, 2024)
In this randomized crossover trial, we found a trend for preference of apalutamide over enzalutamide among patients with predominantly low-volume recurrent or metastatic prostate cancer and their physicians and caregivers. Fewer side effects is the most critical factor influencing treatment preference. Treatment preference regarding apalutamide versus enzalutamide in prostate cancer (PCa) and the factors influencing decisions are largely unknown. Our aim was to investigate the preference for apalutamide versus enzalutamide among prostate cancer patients and their physicians and caregivers, and factors influencing their decision. This was a prospective, open-label, randomized, crossover trial. Patients with recurrence of localized PCa or with metastatic disease not considered as high-risk or high-volume and on continued androgen deprivation therapy were recruited. All subjects received a trial of two agents, apalutamide (A) and enzalutamide (E), for 12 wk each, with a 5-wk washout period in between. The sequencing of the drugs was randomized. The primary outcome was patient preference for one the drugs, assessed at the end of the study. Other outcomes included factors influencing patient preference, a comparison of side-effect profiles, and patients’ quality of life (QoL). Physician and caregiver preferences for the drugs and factors affecting their choice were also assessed. A total of 74 patients met the eligibility criteria and were randomized to the A → E or E → A arm. Of these, 66 patients (89.1%; 32 A → E, 34 E → A) completed the study. Baseline characteristics were comparable between the two groups, and ∼90% of the patients had low-volume metastatic disease. After completion of both treatments for 12 wk each, the difference in preference for A over E was 17.8%, with similar trends for preference of A over E among physicians (18.2%) and caregivers (22.4%). Fewer side effect was the most critical factor influencing the preference of patients. Among the side effects, less fatigue was the benefit of A over E most frequently reported. No notable difference in QoL was observed between the two drugs. However, the study was terminated on interim analysis and the results might not be conclusive. There was a trend for preference of A over E among patients with predominantly low-volume recurrent or metastatic PCa and their physicians and caregivers. Fewer side effects was the most critical factor influencing their choice. Patients with low-volume recurrent or metastatic prostate cancer tended to prefer treatment with apalutamide over enzalutamide. Side effects were the most critical factor influencing treatment preference.